2015
DOI: 10.5152/akd.2014.5730
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of floating wire and single wire techniques in right coronary ostial lesions in terms of procedural features and one-year clinical follow-up results

Abstract: Objective:The floating wire technique is a special technique for solving interventional problems in aortaostial lesions. There are no long-term data in the literature for the floating wire technique in right aorto-ostial lesions.Methods:One hundred twenty six patients were retrospectively analyzed in this study. All of these patients had a critical right coronary aortoostial lesion. The floating wire technique was performed on 64 patients, and the single wire technique was performed on 62 patients. The two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The importance of these procedures is now better understood. There was no DES-treated control group, and the heterogeneity in the protocols, cohorts under study, and outcomes of previously published studies complicates any comparison 11,[22][23][24][25][26][27][28][29] . In addition, operator preference at the time of the choice of the device (BVS versus DES) might have introduced a patient/lesion selection bias.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these procedures is now better understood. There was no DES-treated control group, and the heterogeneity in the protocols, cohorts under study, and outcomes of previously published studies complicates any comparison 11,[22][23][24][25][26][27][28][29] . In addition, operator preference at the time of the choice of the device (BVS versus DES) might have introduced a patient/lesion selection bias.…”
Section: Limitationsmentioning
confidence: 99%
“…Predilation was performed in 97% of the lesions (vs. 96% in non-ostial, p=0.618), post-dilation in 43% (versus 58% in the non-ostial group, p=0.008). At quantitative coronary angiography, treatment of ostial lesions was associated with higher residual stenosis (30% [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] vs. 26% [20-37], p=0.035), but no difference in minimum lumen diameter existed (p=0.447). Follow-up data were available at 385 days.…”
mentioning
confidence: 99%
“…[19][20][21] Accurate stent localization and deployment are important in preventing in-stent restenosis and TLR. 10,22,23) In this study, a randomized comparison between BBT and BWT for assisted PCI showed that BBT had an advantage over BWT, was simple to perform, and safe for the accurate placement of stents in either ostial or non-ostial coronary lesions. Previous studies suggested various adjunctive techniques to help reduce the pulsatile motion of stents caused by cardiac contractions prior to deployment; however, these techniques are associated with certain limitations.…”
Section: Discussionmentioning
confidence: 78%
“…When long-term outcomes were compared between the floating wire method and the direct single stenting method performed for RCA ostial lesions, the floating wire method was found to be significantly better in operational and clinical follow-up outcomes. 4 In this method, to clearly locate the coronary ostium, nonhydrophilic guidewires were used as the second wire in the aortic root. The buddy balloon anchor stenting method is one method used in all ostial lesions, including aorto-ostial lesions, with good follow-up outcomes.…”
Section: Discussionmentioning
confidence: 99%